Ceramic clay and method for its production
Patent Information
- Application Number
- CN202410724071.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-06-05
AI Technical Summary
[0005]本发明的目的在于提供一种陶瓷泥料及其制备方法,以解决现有陶瓷泥料以有机物作为粘接剂制品强度低的问题
本发明提供一种陶瓷泥料,以羧甲基纤维素钠原位接枝纳米氧化锌作为有机无机杂化粘接剂,替代现有羧甲基纤维素钠纯有机粘接剂,不仅发挥良好的粘接、增塑作用,且高温烧结后,纳米氧化锌能够弥补羧甲基纤维素钠分解产生的缺陷,有利于降低陶瓷泥料烧结过程中的收缩率,此外,纳米氧化锌还具有良好的杀菌性能,能够赋予陶瓷制品良好的抗菌性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic manufacturing technology, specifically relating to a ceramic clay and its preparation method. Background Technology
[0002] Ceramic clay, also known as ceramic mortar, is a widely used material in ceramic production. Its main characteristics include high binding strength, plasticity, and good sintering properties. When fired at high temperatures, ceramic clay can form porcelain products with high hardness, a fine texture, and a translucent appearance.
[0003] Ceramic clay generally consists of inorganic non-metallic materials, binders, water, and other auxiliary materials. Inorganic non-metallic materials are further divided into: plastic raw materials, including clays such as Datong clay, which mainly play a role in plasticization and bonding during production and are crucial for ceramic forming; lean raw materials, including quartz minerals; and fluxing raw materials, including potassium feldspar minerals. The basic requirements for ceramic clay are that the particle size of the inorganic non-metallic materials must be controlled between several micrometers and tens of micrometers, with uniform particle distribution, no agglomeration, low binding strength, and good fluidity. The balance between viscosity and fluidity is critical.
[0004] Most of the binders in existing ceramic clay are organic materials. Although they play a corresponding role in bonding and plasticizing, the decomposition of organic materials during sintering will lead to a decrease in the overall density of the ceramic clay and an increase in porosity, which in turn will reduce the strength of the finished product. Summary of the Invention
[0005] The purpose of this invention is to provide a ceramic clay and its preparation method to solve the problem of low strength in existing ceramic clay products using organic materials as binders.
[0006] The objective of this invention can be achieved through the following technical solutions: A ceramic clay material includes a clay base, a dispersant, a zirconium phosphate-based reinforcing component, an organic-inorganic hybrid binder, and water. The zirconium phosphate-based reinforcing component accounts for 3-8% of the clay base, the dispersant accounts for 0.1-0.3% of the clay base, the organic-inorganic hybrid binder accounts for 1-5% of the clay base, and the water accounts for 30-35% of the clay base.
[0007] The clay base material comprises the following raw materials in parts by weight: 32-41 parts Datong clay, 6-10 parts potassium feldspar, 15-20 parts quartz, 20-25 parts clay, 3-5 parts dolomite, and 0.5-1 parts barium carbonate.
[0008] The organic-inorganic hybrid adhesive is sodium carboxymethyl cellulose in situ grafted with nano zinc oxide.
[0009] Furthermore, the organic-inorganic hybrid adhesive is prepared through the following steps: Sodium carboxymethyl cellulose was added to an aqueous solution of zinc nitrate hexahydrate and stirred until homogeneous to obtain mixture a. An aqueous solution of triethanolamine was added to anhydrous ethanol to obtain mixture b. Mixtures a and b were added to a mixing tank and stirred for 1 hour. The mixture was then transferred to a polytetrafluoroethylene reactor and rapidly heated to 180°C at 600W for 15 minutes using a microwave digester. After cooling to room temperature, the mixture was centrifuged. The precipitate was washed three times with ethanol and deionized water and dried at 60°C to constant weight. In the above process, the ratio of zinc nitrate hexahydrate aqueous solution, sodium carboxymethyl cellulose, triethanolamine aqueous solution, and anhydrous ethanol is 100mL:0.1-0.5g:100mL:10-100mL. The concentration of zinc nitrate hexahydrate aqueous solution is 0.01-0.06mol / L, and the concentration of triethanolamine aqueous solution is 1.2mol / L. Using zinc nitrate hexahydrate and triethanolamine as raw materials, nano-ZnO is prepared by microwave hydrothermal method. At the same time, sodium carboxymethyl cellulose is introduced in situ for graft modification to obtain an organic-inorganic hybrid adhesive.
[0010] Furthermore, the zirconium phosphate-based reinforcing component is prepared through the following steps: Carboxyl-containing polycarbosilane was added to xylene to obtain mixture c. Nano-silver-loaded zirconium phosphate was dispersed in a flask containing anhydrous ethanol. Mixture c was added dropwise to the flask at 45°C. After the addition was completed, the mixture was stirred and kept warm for 2 hours. After cooling to room temperature, it was filtered, and the filter cake was washed and dried to obtain the zirconium phosphate-based reinforcing component.
[0011] Furthermore, the ratio of carboxyl-containing polycarbosilane, xylene, nano-silver-loaded zirconium phosphate, and anhydrous ethanol is 1-2g: 10-20mL: 10g: 100-150mL.
[0012] The surface of nano-silver-loaded zirconium phosphate is modified with carboxyl-containing polycarbosilane, which binds to the nano-silver-loaded zirconium phosphate through hydrogen bonding and other interactions. This improves the dispersibility of the nano-silver-loaded zirconium phosphate in ceramic clay and, as a precursor to SiC fibers, forms the SiC phase in the ceramic product during the sintering process, thereby increasing the strength of the ceramic product.
[0013] Furthermore, the carboxyl-containing polycarbosilane is prepared by the following steps: After mixing polycarbosilane and tetrahydrofuran, transfer the mixture to a flask, heat it to 80°C under nitrogen protection, add acrylic acid and chloroplatinic acid, stir and heat to 100-120°C, keep the temperature for 8-20 hours, and after the reaction is completed, remove the tetrahydrofuran by vacuum distillation. In the above reaction, the mass ratio of polycarbosilane to acrylic acid is 1:0.2-0.5, and the amount of chloroplatinic acid is 0.002% of the total mass of polycarbosilane and acrylic acid. The polycarbosilane containing Si-H bonds and the base material undergo a hydrosilylation reaction with the acrylic acid containing C=C bonds to obtain a carboxyl-containing polycarbosilane.
[0014] Furthermore, the M of polycarbosilane n Its concentration is 1084-1387 g / mol, its molecular weight (Mw) is 2492-7963 g / mol, and its softening point is 206-260℃.
[0015] Furthermore, the dispersant is any one or more of glycerol, trioleic acid glyceride, and triethanolamine.
[0016] The method for preparing the above-mentioned ceramic clay includes the following steps: According to the formula ratio, Datong clay, potassium feldspar, quartz, clay, dolomite, barium carbonate, dispersant, zirconium phosphate-based reinforcing component, organic-inorganic hybrid binder, and water are added to a ball mill jar and ball milled using a planetary ball mill. The parameters of the planetary ball mill are set as follows: rotation speed 350-400 r / min, rotation time 10-20 min, to obtain slurry. The slurry is aged in a slurry tank at a temperature of 30-50℃ and a humidity of 60-80% for 40-60 hours. Then, the slurry is filtered at a pressure of 1.4-1.5 MPa to obtain mud cake. The mud cake is added to a ply mill and ply twice to obtain mud strips. The mud strips are aged in an aging chamber for 6-9 days at a temperature of 30-50℃ and a humidity of 60-80%, and then ply three more times. The moisture content of the pounded mud is 20-22 wt%, resulting in ceramic clay.
[0017] The beneficial effects of this invention are: This invention provides a ceramic clay material that uses sodium carboxymethyl cellulose in situ grafted with nano-zinc oxide as an organic-inorganic hybrid binder, replacing the existing pure organic binder sodium carboxymethyl cellulose. This not only provides excellent adhesion and plasticizing effects, but also, after high-temperature sintering, the nano-zinc oxide can compensate for the defects caused by the decomposition of sodium carboxymethyl cellulose, which helps to reduce the shrinkage rate of the ceramic clay material during sintering. In addition, the nano-zinc oxide also has good bactericidal properties, which can endow ceramic products with good antibacterial properties.
[0018] This invention also incorporates a zirconium phosphate-based reinforcing component into the ceramic clay, which is obtained by combining carboxyl-containing polycarbosilane and nano-silver-loaded zirconium phosphate. Carboxyl-containing polycarbosilane is introduced onto the surface of the nano-silver-loaded zirconium phosphate. First, it improves the dispersibility of nano-silver-loaded zirconium phosphate in ceramic clay, ensuring uniform dispersion within the ceramic matrix. Based on its high thermal stability, this imparts thermal stability, antibacterial properties, and mechanical strength to ceramic products. Second, it acts as an organic binder. During sintering, the carboxyl groups of carboxyl-containing polycarbosilane react with the hydroxyl groups of the organic-inorganic hybrid binder to generate an organic network. This network enhances the interaction between matrix particles, further increasing the density of the ceramic clay. Third, it serves as a SiC fiber precursor, forming a SiC reinforcing phase in ceramic products during sintering, thus improving the strength and thermal stability of the ceramic products. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] In the following embodiments and comparative examples: Silver-loaded zirconium phosphate nanoparticles, industrial grade, 6S-NP3, silver content ≥2.0%, particle size (D50) ≤700nm, purchased from Shanghai Liuli Nanomaterials Technology Co., Ltd. The quartz particle size distribution is as follows: 25 wt% for 180-200 mesh and 75 wt% for 250-350 mesh; The chemical composition of Datong clay is SiO2: 46wt%, Al2O3: 38wt%, loss on ignition: 17wt%, and unavoidable impurities; The chemical composition of the clay is SiO2: 46wt%, Al2O3: 36wt%, loss on ignition: 15wt%, and unavoidable impurities; The chemical composition of potassium feldspar is as follows: SiO2: 70.25 wt%, Al2O3: 16.39 wt%, Fe2O3: 0.11 wt%, K2O: 9.27 wt%, Na2O: 3.13 wt%, IL: 0.85 wt%. The chemical composition of dolomite is CaO: 33.48wt%, MgO: 20.86wt%, P2O5: 0.17wt%, SiO2: 0.75wt%, Fe2O3: 0.12wt%, Al2O3: 0.07wt%, and loss on ignition: 44.55wt%.
[0021] Example 1 The zirconium phosphate-based reinforcing component is prepared through the following steps: 1g of carboxyl-containing polycarbosilane was added to 10mL of xylene to obtain mixture c. 10g of nano-silver-loaded zirconium phosphate was dispersed in a flask containing 100mL of anhydrous ethanol. Mixture c was added dropwise to the flask at 45℃. After the addition was completed, the mixture was stirred and kept warm for 2h. After cooling to room temperature, it was filtered. The filter cake was washed with deionized water and anhydrous ethanol and then dried in an oven at 90℃ for 24h to obtain the zirconium phosphate-based reinforcing component.
[0022] Carboxyl-containing polycarbosilanes are prepared by the following steps: Mix 10g of polycarbosilane and 100mL of tetrahydrofuran and transfer to a flask. Under nitrogen protection, heat to 80℃, add 2g of acrylic acid and chloroplatinic acid, stir and heat to 100℃, and keep the reaction at this temperature for 8 hours. After the reaction is complete, remove the tetrahydrofuran by vacuum distillation. The amount of chloroplatinic acid used is 0.002% of the total mass of polycarbosilane and acrylic acid.
[0023] M of polycarbosilane n The concentration is 1084 g / mol, the Mw is 2492 g / mol, and the softening point is 206℃. It was provided by the Ningbo Institute of Materials Technology and Engineering, Chinese Academy of Sciences.
[0024] Example 2 The zirconium phosphate-based reinforcing component is prepared through the following steps: 2g of carboxyl-containing polycarbosilane was added to 20mL of xylene to obtain mixture c. 10g of nano-silver-loaded zirconium phosphate was dispersed in a flask containing 150mL of anhydrous ethanol. Mixture c was added dropwise to the flask at 45℃. After the addition was completed, the mixture was stirred and kept warm for 2h. After cooling to room temperature, it was filtered. The filter cake was washed with deionized water and anhydrous ethanol and then dried in an oven at 90℃ for 24h to obtain the zirconium phosphate-based reinforcing component.
[0025] Carboxyl-containing polycarbosilanes are prepared by the following steps: Mix 10g of polycarbosilane and 100mL of tetrahydrofuran and transfer to a flask. Under nitrogen protection, heat to 80℃, add 5g of acrylic acid and chloroplatinic acid, stir and heat to 120℃, and keep the reaction at this temperature for 20h. After the reaction is complete, remove the tetrahydrofuran by vacuum distillation. The amount of chloroplatinic acid used is 0.002% of the total mass of polycarbosilane and acrylic acid.
[0026] M of polycarbosilane n The concentration is 1387 g / mol, the Mw is 7963 g / mol, and the softening point is 260℃. It was provided by the Ningbo Institute of Materials Technology and Engineering, Chinese Academy of Sciences.
[0027] Comparative Example 1 The zirconium phosphate-based reinforcing component is prepared through the following steps: 1 g of polycarbosilane was added to 10 mL of xylene to obtain mixture c. 10 g of nano-silver-loaded zirconium phosphate was dispersed in a flask containing 100 mL of anhydrous ethanol. Mixture c was added dropwise to the flask at 45 °C. After the addition was complete, the mixture was stirred and kept at this temperature for 2 h. The mixture was then cooled to room temperature, filtered, and the filter cake was washed with deionized water and anhydrous ethanol and dried in an oven at 90 °C for 24 h to obtain the zirconium phosphate-based reinforcing component, polycarbosilane M. n Mw and softening point are the same as in Example 1.
[0028] Comparative Example 2 This comparative example is nano-silver-loaded zirconium phosphate.
[0029] Example 3 A ceramic clay material includes a clay base, glycerol, a zirconium phosphate-based reinforcing component of Example 1, an organic-inorganic hybrid binder, and water. The zirconium phosphate-based reinforcing component accounts for 3% of the clay base, the glycerol accounts for 0.1% of the clay base, the organic-inorganic hybrid binder accounts for 1% of the clay base, and the water accounts for 30% of the clay base.
[0030] The clay base material comprises the following raw materials in parts by weight: 32 parts Datong clay, 6 parts potassium feldspar, 15 parts quartz, 20 parts clay, 3 parts dolomite, and 0.5 parts barium carbonate.
[0031] Organic-inorganic hybrid adhesives are prepared through the following steps: Add 0.1 g of sodium carboxymethyl cellulose to 100 mL of 0.01 mol / L zinc nitrate hexahydrate aqueous solution and stir until homogeneous to obtain mixture a. Add 100 mL of 1.2 mol / L triethanolamine aqueous solution to 10 mL of anhydrous ethanol to obtain mixture b. Add mixture a and mixture b to a stirred tank and stir for 1 h. Transfer the mixture to a polytetrafluoroethylene reactor and rapidly heat to 180 °C at 600 W for 15 min using a microwave digester. After cooling to room temperature, centrifuge the mixture. Wash the precipitate three times with ethanol and deionized water and dry it at 60 °C to constant weight.
[0032] The method for preparing the above-mentioned ceramic clay includes the following steps: According to the formula ratio, Datong clay, potassium feldspar, quartz, clay, dolomite, barium carbonate, dispersant, zirconium phosphate-based reinforcing component, organic-inorganic hybrid binder, and water were added to a ball mill jar and ball milled using a planetary ball mill. The parameters of the planetary ball mill were set as follows: rotation speed 350 r / min, rotation time 10 min, to obtain slurry. The slurry was aged in a slurry tank at a temperature of 30℃ and humidity of 60% for 40 h. After that, the slurry was filtered at a pressure of 1.4 MPa to obtain mud cake. The mud cake was added to a ply mill and plyed twice to obtain mud strips. The mud strips were aged in an aging chamber for 6 days at a temperature of 30℃ and humidity of 60%, and then plyed three more times. The moisture content of the slurry after plying was 20 wt%, resulting in ceramic clay.
[0033] Example 4 A ceramic clay material includes a clay base, trioleic acid glyceride, a zirconium phosphate-based reinforcing component as described in Example 2, an organic-inorganic hybrid binder, and water. The zirconium phosphate-based reinforcing component accounts for 5% of the clay base, the trioleic acid glyceride accounts for 0.2% of the clay base, the organic-inorganic hybrid binder accounts for 3% of the clay base, and the water accounts for 32% of the clay base.
[0034] The clay base material comprises the following raw materials in parts by weight: 38 parts Datong clay, 8 parts potassium feldspar, 18 parts quartz, 22 parts clay, 4 parts dolomite, and 0.8 parts barium carbonate.
[0035] Organic-inorganic hybrid adhesives are prepared through the following steps: Add 0.3 g of sodium carboxymethyl cellulose to 100 mL of 0.02 mol / L zinc nitrate hexahydrate aqueous solution and stir until homogeneous to obtain mixture a. Add 100 mL of 1.2 mol / L triethanolamine aqueous solution to 50 mL of anhydrous ethanol to obtain mixture b. Add mixture a and mixture b to a stirred tank and stir for 1 h. Transfer the mixture to a polytetrafluoroethylene reactor and rapidly heat to 180 °C at 600 W for 15 min using a microwave digester. After cooling to room temperature, centrifuge the mixture. Wash the precipitate three times with ethanol and deionized water and dry it at 60 °C to constant weight.
[0036] The method for preparing the above-mentioned ceramic clay includes the following steps: According to the formula ratio, Datong clay, potassium feldspar, quartz, clay, dolomite, barium carbonate, dispersant, zirconium phosphate-based reinforcing component, organic-inorganic hybrid binder, and water were added to a ball mill jar and ball milled using a planetary ball mill. The parameters of the planetary ball mill were set as follows: rotation speed 3800 r / min, rotation time 15 min, to obtain slurry. The slurry was aged in a slurry tank at a temperature of 40℃ and a humidity of 70% for 50 h. After that, the slurry was filtered at a pressure of 1.4 MPa to obtain mud cake. The mud cake was added to a ply mill and plyed twice to obtain mud strips. The mud strips were aged in an aging chamber for 8 days at a temperature of 40℃ and a humidity of 70%, and then plyed three more times. The moisture content of the slurry after plying was 21 wt%, resulting in ceramic clay.
[0037] Example 5 A ceramic clay material includes a clay base, a triethanolamine dispersant, a zirconium phosphate-based reinforcing component as described in Example 2, an organic-inorganic hybrid binder, and water. The zirconium phosphate-based reinforcing component accounts for 8% of the clay base, the triethanolamine accounts for 0.3% of the clay base, the organic-inorganic hybrid binder accounts for 5% of the clay base, and the water accounts for 35% of the clay base.
[0038] The clay base material comprises the following raw materials in parts by weight: 41 parts Datong clay, 10 parts potassium feldspar, 20 parts quartz, 25 parts clay, 5 parts dolomite, and 1 part barium carbonate.
[0039] Organic-inorganic hybrid adhesives are prepared through the following steps: Add 0.5 g of sodium carboxymethyl cellulose to 100 mL of 0.06 mol / L zinc nitrate hexahydrate aqueous solution and stir until homogeneous to obtain mixture a. Add 100 mL of 1.2 mol / L triethanolamine aqueous solution to 100 mL of anhydrous ethanol to obtain mixture b. Add mixture a and mixture b to a stirred tank and stir for 1 h. Transfer the mixture to a polytetrafluoroethylene reactor and rapidly heat to 180 °C at 600 W for 15 min using a microwave digester. After cooling to room temperature, centrifuge the mixture. Wash the precipitate three times with ethanol and deionized water and dry it at 60 °C to constant weight.
[0040] The method for preparing the above-mentioned ceramic clay includes the following steps: According to the formula ratio, Datong clay, potassium feldspar, quartz, clay, dolomite, barium carbonate, dispersant, zirconium phosphate-based reinforcing component, organic-inorganic hybrid binder, and water were added to a ball mill jar and ball milled using a planetary ball mill. The parameters of the planetary ball mill were set as follows: rotation speed 400 r / min, rotation time 20 min, to obtain slurry. The slurry was aged in a slurry tank at a temperature of 50℃ and humidity of 80% for 60 h. After that, the slurry was filtered at a pressure of 1.5 MPa to obtain mud cake. The mud cake was added to a ply mill and plyed twice to obtain mud strips. The mud strips were aged in an aging chamber for 9 days at a temperature of 50℃ and humidity of 80%, and then plyed three more times. The moisture content of the slurry after plying was 22 wt%, resulting in ceramic clay.
[0041] Comparative Example 3 A ceramic clay, compared with Example 3, replaces the zirconium phosphate-based reinforcing component in Example 3 with the substance in Comparative Example 1, while the remaining raw materials and preparation process are the same as in Example 3.
[0042] Comparative Example 4 A ceramic clay, compared with Example 3, replaces the zirconium phosphate-based reinforcing component in Example 3 with the substance in Comparative Example 2, while the remaining raw materials and preparation process are the same as in Example 3.
[0043] Comparative Example 5 A ceramic clay, compared with Example 3, replaces the organic-inorganic hybrid binder in Example 3 with "a mixture of nano zinc oxide and sodium carboxymethyl cellulose in a mass ratio of 0.08:0.1", and the other raw materials and preparation process are the same as in Example 3.
[0044] Comparative Example 6 A ceramic clay, compared with Example 3, replaces the organic-inorganic hybrid binder in Example 3 with sodium carboxymethyl cellulose, while the other raw materials and preparation process are the same as in Example 3.
[0045] The ceramic clay materials obtained in Examples 3-5 and Comparative Examples 3-6 were placed in a strip mold and allowed to stand for 12 hours to form. The formed ceramic strips were dried at 110°C for 3 hours, then heated to 1150°C at a heating rate of 5°C / min and calcined for 3 hours. The temperature was then slowly lowered to room temperature to obtain the ceramic material. The shrinkage rate of the ceramic strips was tested. Different samples (10 per group) were prepared according to GB / T 4740-1999, and the compressive strength of the different samples was tested (average value was taken). The antibacterial rate of the ceramic material against Escherichia coli and Staphylococcus aureus was tested according to JC / T 897-2002 "Antibacterial Properties of Antibacterial Ceramic Products". The results are shown in Table 1. Table 1
[0046] As can be seen from the data recorded in Table 1, compared with Comparative Examples 3-6, the ceramic materials obtained in Examples 3-5 have lower shrinkage, higher compressive strength, and better antibacterial properties. More specifically, the test results of Example 3 and Comparative Example 3 show that carboxylation modification of polycarbosilane is beneficial to reducing the shrinkage of ceramic materials and improving compressive strength. The test results of Example 3 and Comparative Example 4 show that introducing carboxyl-containing polycarbosilane onto the surface of nano-silver-loaded zirconium phosphate can significantly reduce the shrinkage of ceramic materials and improve compressive strength. The test results of Example 3 and Comparative Examples 5 and 6 show that the organic-inorganic hybrid binder in this case is more effective than the combination of nano-zinc oxide and sodium carboxymethyl cellulose or the use of sodium carboxymethyl cellulose alone.
[0047] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0048] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A ceramic clay, characterized in that, The composition includes clay matrix, dispersant, zirconium phosphate-based reinforcing component, organic-inorganic hybrid binder, and water. The amount of zirconium phosphate-based reinforcing component added is 3-8% of the clay matrix, the amount of dispersant added is 0.1-0.3% of the clay matrix, the amount of organic-inorganic hybrid binder added is 1-5% of the clay matrix, and the amount of water added is 30-35% of the clay matrix. The organic-inorganic hybrid adhesive is sodium carboxymethyl cellulose in situ grafted with nano zinc oxide; Zirconium phosphate-based reinforcing components are prepared through the following steps: Carboxyl-containing polycarbosilane was added to xylene to obtain mixture c. Nano-silver-loaded zirconium phosphate was dispersed in a flask containing anhydrous ethanol. Mixture c was added dropwise to the flask at 45°C. After the addition was completed, the mixture was stirred and kept warm for 2 hours. After cooling to room temperature, it was filtered, and the filter cake was washed and dried to obtain the zirconium phosphate-based reinforcing component.
2. The ceramic clay according to claim 1, characterized in that, The clay base material comprises the following raw materials in parts by weight: 32-41 parts Datong clay, 6-10 parts potassium feldspar, 15-20 parts quartz, 20-25 parts clay, 3-5 parts dolomite, and 0.5-1 parts barium carbonate.
3. The ceramic clay according to claim 1, characterized in that, The ratio of carboxyl-containing polycarbosilane, xylene, nano-silver-loaded zirconium phosphate, and anhydrous ethanol is 1-2g: 10-20mL: 10g: 100-150mL.
4. The ceramic clay according to claim 1, characterized in that, Carboxyl-containing polycarbosilanes are prepared by the following steps: After mixing polycarbosilane and tetrahydrofuran, transfer the mixture to a flask. Under nitrogen protection, heat the mixture to 80°C, add acrylic acid and chloroplatinic acid, stir, and then heat to 100-120°C. Maintain the temperature for 8-20 hours. After the reaction is complete, remove the tetrahydrofuran by vacuum distillation.
5. The ceramic clay according to claim 4, characterized in that, The mass ratio of polycarbosilane to acrylic acid is 1:0.2-0.5, and the amount of chloroplatinic acid used is 0.002% of the total mass of polycarbosilane and acrylic acid.
6. The method for preparing ceramic clay according to claim 1, characterized in that, Includes the following steps: According to the formula ratio, Datong clay, potassium feldspar, quartz, clay, dolomite, barium carbonate, dispersant, zirconium phosphate-based reinforcing component, organic-inorganic hybrid binder, and water are added to a ball mill jar and ball milled using a planetary ball mill to obtain slurry. The slurry is aged in a slurry tank for 40-60 hours, and then filtered to obtain mud cake. The mud cake is added to a ply mill and ply twice to obtain mud strips. The mud strips are aged in an aging chamber for 6-9 days, and then ply three more times. The moisture content of the ply clay is 20-22 wt%, which yields ceramic clay.
Citation Information
Patent Citations
Antibacterial ceramic raw material
CN109095886A
High-silicon high-grade daily fine porcelain pug as well as plasticizing preparation method and application of high-silicon high-grade daily fine porcelain pug
CN115784709A